Reformulating Indonesia’s Narcotics Law on Personal Drug Misuse: A Humanist Approach - Pakpahan, Hartato; Nurjaya, I Nyoman; Nurdayasakti, Setiawan; Aprilianda, Nurini (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2024)
This study explores the development of more equitable and humane regulations for addressing personal drug misuse in Indonesia, emphasizing a humanist perspective and the principles of restorative justice. Employing a normative legal research methodology, the study critically examines Articles 111–127 of Law Number 35 of 2009 on Narcotics. It also incorporates a comparative analysis of drug policies in countries that have successfully implemented decriminalization and mandatory rehabilitation, such as the Netherlands and Portugal. The findings highlight the limitations of Indonesia's repressive approach, which often exacerbates social marginalization and fails to address the root causes of addiction. In contrast, the rehabilitative models adopted by the Netherlands and Portugal have proven more effective in reducing the negative impacts of drug abuse and fostering reintegration into society. To alleviate the burden on the criminal justice system and promote a more inclusive society, this study recommends legislative reforms that prioritize social rehabilitation and reintegration over punitive measures. These changes aim to shift Indonesia's drug policy toward a more compassionate and effective framework, balancing public health, social equity, and justice.